Computation of relative integral bases for algebraic number fields - Mahmood Haghighi (International Journal of Mathematics and Mathematical Sciences)
At first we are given conditions for existence of relative integral bases for extension (K;k)=n. Then we will construct relative integral bases for extensions OK6(−36)/Ok2(−3), OK6(−36)/Ok3(−33), OK6(−36)/Z.